Introduction to Chest Wall Reconstruction: Anatomy and Physiology of the Chest and Indications for Chest Wall Reconstruction - Clemens, Mark W. (Thieme Medical Publishers, 2011)
The chest wall functions as a protective cage around the vital organs of the body, and significant disruption of its structure can have dire respiratory and circulatory consequences. The past several decades have seen a marked improvement in the management and reconstruction of complex chest wall defects. Widespread acceptance of muscle and musculocutaneous flaps such as the latissimus dorsi, pectoralis major, serratus anterior, and rectus abdominis has led to a sharp decrease in infections and mortality. Successful reconstructions are dependent upon a detailed knowledge of the functional anatomy and blood supply of the chest and the underlying pathophysiology of a particular disease process. This article will provide an overview of key principles and evidence-based approaches to chest wall reconstruction.